THE EFFECTS OF GRAMMAR MASTERY AND VOCABULARY MASTERY TOWARDS STUDENTS' READING COMPREHENSION IN EXPOSITORY TEXT - Etik Dwi Styaningrum (LPPM Universitas Bina Sarana Informatika, 2019)
The main aim of the research is to find out whether there is significant effects of Grammar Mastery and Vocabulary Mastery towards Students’ Reading Comprehension in Expository Text. The research was conducted at SMKN 1 Cikarang of tenth grade students with the total sample 40 students that randomly taken and at SMKN 2 Cikarang of tenth grade students with the total samples 40 students that randomly taken. The method used in the research was a survey. Data of grammar mastery, vocabulary mastery and reading comprehension were acquired from the tests. The data was analysed using descriptive statistical method, multiple correlation coefficient, determination coefficient and regression analysis. To test the statistics is used T test and F test . The result of the research concluded that there are significant effect of Grammar mastery and vocabulary mastery towards student’s reading comprehension in expository text.